SHARIA HEDGING : PROFIT OR LOSS? - Hernawaty Hernawaty; Nurhayati Nurhayati (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to determine the point of view of market players who use sharia hedging in developing countries. This study aims to examine in depth the benefits and problems of implementing sharia hedging. The methodology or approach used in this research is to use a library research method or approach by collecting, discussing and providing views on some of the results of previous research. The results of this study obtained several different views from market players looking at the advantages and disadvantages of using sharia hedging. More Islamic assets are able to survive in times of economic recession than conventional assets. This raises the enthusiasm of investors in the Islamic financial market. On the other hand, the Islamic financial risk management market which is still in its early stages and the limited use of hedging instruments are obstacles that cannot be underestimated. Sharia hedging can be considered useful or profitable if it is reviewed to the original purpose of its use, namely minimizing risk.Keywords: Islamic, Hedging, Risk, Profit, Loss